Gerakan Hijrah Kaum Muda Muslim di Medan (Studi Kasus Gerakan Komunitas Sahabat Hijrahkuu) - Sahran Saputra; Pujiati Pujiati; Muba Simanihuruk; Rizabuana Ismail; Henry Sitorus (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
The research is about migration movement by Sahabat Hijrakuu community as a new social movement of young Muslims in Medan. The objective of the research was to find outits patterns through some articulation typology of Islamic social movement. The research used qualitative method, and the data were gathered by conducting observation, interviews, and library research.The result of the research shows that the development of migration movement is the series and the collective awareness of young Muslims in Medan in the post-Islam Defense Action movement.Referring to articulation typology of Islamic social movement, it is accurate if its pattern is positioned as religion based-social movement since its idea is based on religious attitude of its initiators as a spiritual response to social and spiritual condition of young Muslims in Medan.